George W. Mixter papers - Mixter, George W. (George Webber), 1876-1947.
Correspondence, writings, notes, lectures, ship's papers, problem sets, calculations, maps, and other papers chiefly relating to Mixter's contributions to the study of navigation. Includes material relating to his schooner Teragram and the Bermuda Races of 1932 and 1934. Correspondents include Julius Frederick Hellweg, James Robertson, John Shesta, and Philip Van Horn Weems.
Navigation researcher and consulting engineer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hellweg, Julius Frederick -- Correspondence; Robertson, James -- Correspondence; Shesta, John -- Correspondence; Weems, Philip Van Horn, -- 1889- -- Correspondence; Teragram (Schooner); Navigation; Ship's papers -- 20th century; Yachting -- Bermuda Islands; Engineers; Researchers